SOCIAL VALUES IN AGNES DAVONAR'S SURAT KECIL UNTUK TUHAN: A STUDY OF LITERARY SOCIOLOGY - Ridwan Ritonga; Amin Said Harahap; Miftahudin; Madah Rahmatan; Aminor; Raden Muhammad Ardiansyah Kurniawan (Prologue: Journal on Language and Literature, 2024)
This research reveals social values using the study of literary sociology in the novel Surat Kecil untuk Tuhan by Agnes Davanor. The study of literary sociology in this study focuses on the literary sociology approach of Rene Wellek and Austin Warren. This research is a Literature Study. The data were analyzed using descriptive techniques in the form of the author's speech in the novel Surat Kecil untuk Tuhan by Agnes Davonar. Data collection techniques from books and journals, obtained in accordance with the problems and objectives of literary studies related to social values and literary sociology studies with data sources of Surat Kecil untuk Tuhan novels by Agnes Davanor. The results of research on social values depicted in the novel Surat Kecil untuk Tuhan by Agnes Davanor in literary analysis, namely Compassion, are realized in the form of caring, devotion, kinship, please help. Responsibility, presented in the form of a sense of belonging, discipline, and empathy.